The Effect of Mild Sleep Deprivation on Students’ Cognitive Function during Covid-19 Pandemic - Galang Lufityanto; Samudera Fadlilla Jamaluddin; Alissa Nurfathia; Bernardus Aji (Faculty of Psychology, Universitas Gadjah Mada, 2022)
Covid-19 pandemic has altered students' sleep patterns due to increasing academic demands as a compromise to switching the learning mode from direct classroom interaction to online learning. As a result, some believed it would affect the quality of cognitive functions. We conducted one experiment involving 200 undergraduate students to measure their inhibitory control -a segment of cognitive process that allows controlling the unnecessary but often striking impulses – under two conditions, i.e., sufficient sleep and lack of sleep. Participants were asked to record their regular sleeping hours a week before the measurement period to get the baseline condition. Lack of sleep condition was determined by taking only partitions (less than 85%) of the regular sleeping hours overnight. Inhibitory control was measured using the online version of Simon Task about 30 minutes after the participants woke up in the morning. We found no direct effect of sleep deprivation on the performance of the Simon Task. Participants performed the Simon Task comparably well between the Sleep Deprived and Sufficient Sleep conditions. However, sleep deprivation inhibited the learning process required to perform identical Simon Task on the subsequent measurement intake. Our finding demonstrates that despite no empiric evidence of the direct impact of sleep deprivation on cognitive function per se, it affects the covert learning process required to perform well in future assignments.